Risk for metabolic syndrome in a group of overweight children from South-East Romania - Chesaru, Bianca I.; Dobre, Michaela; Murariu, Gabriel; Nechita, Aurel (Revista română de medicină de laborator, 2013)
The present study aims to identify and analyse the cardiometabolic risk factors associated with the metabolic syndrome in overweight children and adolescents. The study group included 163 overweight children and adolescents, average age: 13.02 ± 3.42 years. The following evaluations were performed: anthropometrical measurements, blood pressure measurements, biochemical tests investigating the lipid and carbohydrate metabolism. Metabolic syndrome was identified in 48 subjects (29.4%). The risk to develop MS was found to be higher in males and within the 13-18 age group. The most common cardiometabolic risk factors were abdominal obesity (75.5%) and high blood pressure (41.1%), followed by low HDL-cholesterol (35%), increased fasting blood glucose (23.3%) and hypertriglyceridemia (17.8%.). The variables under analysis exhibited significant correlations with the number of metabolic syndrome diagnosis criteria. The metabolic syndrome prevalence in the paediatric population affected by excess body weight has reached high values in our geographical area. It is thus justified to initiate screening activities for the early detection and adequate treatment of the modifiable cardiometabolic risk factors, contributing to the prevention of long-term complications. Studiul de faţa şi-a propus identificarea şi analizarea componen telor cu risc cardiometabolic asociate cu sindromul metabolic la copiii şi adolescenţii cu exces ponderal. Lotul de studiu a inclus un număr de 163 de copii şi adolescenţi cu exces ponderii, cu media de vârstă 13.02 ±3.42 ani. S-au efectuat: măsurători antropometrice, măsurarea tensiunii arteriale şi determinări biochimice pentru investigarea metabolismului lipidic şi glucidic. Prezenţa sindromului metabolic a fost înregistrată la 48 de subiecţi (29.4%). Riscul de a dezvolta SM a fost mai crescut la copiii de sex masculin şi la cei din grupa de vârstă 13-18 ani. Cele mai frecvente componente cu risc cardiometabolic au fost obezitatea abdominală (75.5%) şi hipertensiunea arterială (41.1%), urmate de HDL-colesterol scăzut 35%, glicemic ă jeun crescută (23.3%) şi hipertrigliceridemie (17.8%). Variabilele analizate au prezentat corelaţii semnificative cu numărul de criterii de diagnostic ale sindromului metabolic. Prevalenţa sin- dromului metabolic în populaţia pediatrică cu exces ponderal este crescută în zona noastră geografică. Se justifică ast- fel iniţierea activităţilor de screening pentru depistarea precoce şi intervenţia adecvată asupra factorilor de risc carclio- metabolici modificabili, contribuind în acest mod la prevenirea complicaţiilor acestora pe termen lung